ANALISIS KOMPARASI BAURAN PROMOSI BATARA WATER SPORT SEBELUM PANDEMI DAN SEMASA PANDEMI COVID-19 - Arya Adi Dananjaya; NGAS. Dewi; Putu Agus Wikanatha Sagita (Jurnal IPTA (Industri Perjalanan Wisata), 2021)
During the Covid-19 pandemic, the entire world experienced a decline in all aspects, including the world of tourism and many companies experienced a decline in income due to the corona virus outbreak, one of which is PT. Batara Water Sport, but this company has a way that is able to bring in tourists during this pandemic, the purpose of this study is to find out how different the methods of promotion carried out by PT. Batara Water Sport before the pandemic with during the pandemic, therefore this phenomenon is able to provide the background for this research. The type of data used in this research is qualitative data. The technique of determining the informants in this study is by using purposive sampling with three people as informants, while the data analysis technique uses descriptive qualitative. Collecting data by observation, interviews, literature study, and documentation. The result of this research is the promotion mix used by PT. Batara Water Sport during the pandemic, which is predominantly using electronic media as a media for product promotion designed to bring tourists to companies during the pandemic, such as providing discounts of up to 50%, one free game for consumers who use five games, and there are two special packages provided by companies during the Covid-19 pandemic, in contrast to before the pandemic, which only used printed media such as brochures, were able to bring tourists to the company. In addition to providing attractive promos, during this pandemic the company also implements strict health protocols to be able to break the chain of spreading the Covid-19 virus.